The Dynamics of Regional Head Candidate Selection and its Implications for Local Democracy: A Case Study of Medan City, Indonesia - Ikhsan, Muhammad; ., Subhilhar; Kusmanto, Heri; Nasution, Indra Kesuma (Journal of Ecohumanism, 2024)
This research analyzes the political dynamics in the selection process of regional head candidates in Medan City. Through a qualitative approach, this research reveals the candidate selection process of political parties such as PDIP and Gerindra and its impact on local democracy. The research method involved interviews, FGDs, and descriptive-analytical analysis, focusing on inclusion, transparency, and accountability. The results highlighted that factors such as identity politics, money politics, and central government intervention had a significant impact. Although Regional head Elections is considered a platform for local democracy, the candidate selection process is often still closed and influenced by elitism and oligarchy within political parties. Internal conflicts within political parties demonstrate the dominance of DPP influence and centralization of power within the party. Corruption cases involving local officials highlight the importance of integrity and transparency in clean governance. However, the deliberative model is emerging as an alternative that can improve inclusion, transparency and accountability in the selection process of local head candidates. The deliberative model is proposed as an alternative to enhance a fairer and more democratic selection process. Thus, this research provides insights into the challenges and opportunities in the development of local democracy in Medan City.